2017
DOI: 10.15585/mmwr.mm6605e3
|View full text |Cite
|
Sign up to set email alerts
|

Vital Signs: Noise-Induced Hearing Loss Among Adults — United States 2011–2012

Abstract: IntroductionThe 2016 National Academies of Sciences report “Hearing Health Care for Adults: Priorities for Improving Access and Affordability” included a call to action for government agencies to strengthen efforts to collect, analyze, and disseminate population-based data on hearing loss in adults.MethodsCDC analyzed the most recent available data collected both by questionnaire and audiometric tests of adult participants aged 20–69 years in the 2011–2012 National Health and Nutrition Examination Survey (NHAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
104
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 13 publications
(13 reference statements)
2
104
1
4
Order By: Relevance
“…An analysis of 2011–2012 data from the National Health and Nutrition Examination Survey found that one in four U.S. adults who reported excellent or good hearing had damage to their hearing suggestive of excessive exposure to loud sounds ( 2 ). During a given 24-hour period, persons are exposed to a wide range of loud sounds, including not only those at work, but also at home, school, and places of recreation, thereby complicating the determination of an exposure level that would provide an adequate level of safety to protect hearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of 2011–2012 data from the National Health and Nutrition Examination Survey found that one in four U.S. adults who reported excellent or good hearing had damage to their hearing suggestive of excessive exposure to loud sounds ( 2 ). During a given 24-hour period, persons are exposed to a wide range of loud sounds, including not only those at work, but also at home, school, and places of recreation, thereby complicating the determination of an exposure level that would provide an adequate level of safety to protect hearing.…”
Section: Discussionmentioning
confidence: 99%
“…During 2011–2012, 21 million U.S. adults who reported no exposure to loud or very loud noise at work exhibited hearing damage suggestive of noise-induced hearing loss ( 2 ). In addition to the known risk for hearing damage, nonauditory adverse health outcomes and health risks from excessive environmental sound exposure can include effects on the cardiovascular system, metabolism, blood pressure, body weight, cognition, sleep, mental health, quality of life, and overall well-being ( 1 , 3 , 4 ).…”
mentioning
confidence: 99%
“…[14][15] [16] High sound levels in restaurants and bars can negatively impact the health and quality of life of patrons and employees as hearing loss is the third most common chronic physical condition in the U.S., [17] and noise is the most common 'modifiable environmental cause' of hearing loss which is present in 24% of adults. [18] Noise is also associated with tinnitus, a noise or ringing in the ears, which affects approximately 11% of adults and hyperacusis, an increased sensitivity to sound, which affects approximately 6% of adults. [19][20] [21] Research also shows that noise can contribute to exhaustion and also release cortisol in the body as it is linked to increased stress, [22] [23] hypertension, ischaemic heart disease, stroke [24] and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[27] To address the dangers of noise pollution, the Center for Disease Control and Prevention (CDC) recommends avoiding prolonged exposure to loud environments to prevent noise-induced hearing loss (NIHL). [28] [29] Noise pollution also affects the quality of life. [30] Even for people with normal hearing, noise is a barrier to the enjoyment of communicating, socializing and connecting with colleagues, friends and families through intimate conversation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation